1996
DOI: 10.1021/jp9609646
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transport and Ferrocene Incorporation in Electroactive Fullerene Films

Abstract: Thick (10 μm) C60 films are prepared by sublimation at 575 °C for 5 min on a pyrolytic carbon film electrode. Scanning electron microscopy shows that the fullerene film consists of crystallites of random size and orientation. Raman spectroscopy shows peaks characteristic of C60 films at 273, 495, 773, 1464, and 1571 cm-1. The electrochemistry of these thick films is consistent with a reduction mechanism that is dominated by ion transport. In the proposed mechanism, swelling of the film and direct intercalation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Once the C 60 in the cluster film undergoes reduction (reaction 1), the anion gets stabilized in the cluster film. As discussed in an earlier work, 25 the complexation between the C 60 anion and tetrabutylammonium cation (TBA 1 ) is responsible for the stabilization of reduced species in the cluster film. Szucs et al 30,31 have demonstrated that the cation stabilized reduced films of C 60 remain stable even when exposed to air.…”
Section: Electrocatalysis Using Fc@(c 60 ) N Filmsmentioning
confidence: 90%
See 3 more Smart Citations
“…Once the C 60 in the cluster film undergoes reduction (reaction 1), the anion gets stabilized in the cluster film. As discussed in an earlier work, 25 the complexation between the C 60 anion and tetrabutylammonium cation (TBA 1 ) is responsible for the stabilization of reduced species in the cluster film. Szucs et al 30,31 have demonstrated that the cation stabilized reduced films of C 60 remain stable even when exposed to air.…”
Section: Electrocatalysis Using Fc@(c 60 ) N Filmsmentioning
confidence: 90%
“…Several studies in the past have reported the redox behavior of fullerene films cast on electrode surfaces. 1,16,24,25,29,38 The redox activity of these films depends upon the method of deposition and the medium in which the C 60 film is exposed. For example, the first and second electron reduction waves of C 60 films are merged to yield a broad reduction wave.…”
Section: Electrochemistry Of Fullerene Cluster Films At Conducting Gl...mentioning
confidence: 99%
See 2 more Smart Citations
“…The electrochemical redox-cycling of solid C 60 has been reported under a wide range of experimental conditions which include various deposition procedures such as solvent casting, gas phase, and electrochemical deposition, and a range of contacting solvent systems and electrolyte salts. The interaction of the solid with neutral solution species , and also catalytic processes have been noted. Most extensive work has been published on the redox-cycling of solid C 60 deposited on an electrode and immersed in an acetonitrile solution containing NBu 4 + cations.…”
Section: Introductionmentioning
confidence: 99%